2016
DOI: 10.1177/2397002215625893
|View full text |Cite
|
Sign up to set email alerts
|

Lost in translation? The role of supervisors in lean production

Abstract: Lean production is commonly associated with a small number of hierarchical layers-the lean organization is supposedly a flat one. The belief that 'flatter is better' appears to have become a truism in many academic and managerial circles. However, several empirical studies point to a completely different conclusion-namely that the prototypical supervisory hierarchy under lean production is characterized by narrow spans of control. This article reviews the empirical literature on the lean supervisors, and based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 77 publications
0
25
0
1
Order By: Relevance
“…For workers, it was a matter of coordination. The reasons they gave for empowering an informal supervisor resonate with contingency theory: hierarchical decision-making is effective for coordinating operational processes characterized by task uncertainty or tight coupling (Collins and Hull, 1986;Ingvaldsen and Benders, 2016). Corroborating the findings of Barker (1993, pp.…”
Section: Upward and Downward Pressures For Hierarchymentioning
confidence: 74%
“…For workers, it was a matter of coordination. The reasons they gave for empowering an informal supervisor resonate with contingency theory: hierarchical decision-making is effective for coordinating operational processes characterized by task uncertainty or tight coupling (Collins and Hull, 1986;Ingvaldsen and Benders, 2016). Corroborating the findings of Barker (1993, pp.…”
Section: Upward and Downward Pressures For Hierarchymentioning
confidence: 74%
“…Karlsson & Åhlström, 1996), empirical research on plants with detailed knowledge of the Toyota Production System has indicated that these are characterized by narrow spans of control, with work unit leaders occupying strong positions of formal and informal power (Delbridge et al, 2000;Inamizu, Fukuzawa, Fujimoto, Shintaku & Suzuki, 2014;Ingvaldsen & Benders, 2016). Ingvaldsen and Benders (2016) argued that such arrangements are functional for the just-in-time production process, as supervisors handle coordination, coach workers, facilitate improvement activities, and form a buffer of manpower in the event of production disturbances. Furthermore, supervisors should act as 'benevolent fathers', educating workers but also disciplining them when necessary (Dore, 1973).…”
Section: The Lean-std Debatesmentioning
confidence: 99%
“…The controlling supervisory style demands that employees adopt the supervisors' perspective, interrupts employees' thoughts, feelings or actions and puts pressure on employees to think, feel and behave in certain ways. Such practice of control and command is not uncommon in the lower-skilled occupations, especially in manufacturing industries (Ingvaldsen & Benders 2016), hence presenting a need to address the controlling supervisory style in the training. Hardré and Reeve (2009) recommended incorporating an awareness of the widespread nature of this controlling style into future autonomy-supportive training, encouraging learner to 1become less controlling by being mindful of the reason they adopt a more controlling style and its consequences, (2) desire an autonomy-supportive supervisory style by helping them appreciate the benefit of it, and (3) learn how to practice autonomy-supportive practices.…”
Section: Sdt and Autonomy-supportive Style Trainingmentioning
confidence: 99%